The underestimated risk for complications in immunocompetent patients with herpes zoster: should we change our clinical practice?. (1st June 2021) - Kridin, K.; Cohen, A.D.
Abstract: Linked Article: Forbes et al. Br J Dermatol 2021; 184 :1077–1084 .